Effects of the inclusion of oak tannins in a diet rich in linoleic acid on in vitro rumen biohydrogenation and fermentation in sheep - Carreño D.; Hervás G.; Toral P.G.; Belenguer A.; Frutos P. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
There is a lack void of knowledge about which of the many types of tannins might be more specific and useful, in practice, to interfere with rumen biohydrogenation (BH) and modulate the fatty acid (FA) profile of ruminant derived products without impairing diet utilization. Two in vitro assays with batch cultures of rumen microorganisms were conducted to analyze the effect of an oenological commercial extract of oak tannins, at a practical dose under farm conditions (2% DM), on the rumen BH and fermentation of a diet also supplemented with 2% DM of sunflower oil. In the first experiment (12 h incubations), freeze-dried ruminal digesta were analyzed for FA composition. In the second one (24 h incubations), rumen fermentation parameters and bacterial community were examined. The addition of 2% DM of the oak tannin extract proved (P<0.01) to be able to slightly reduce the concentration of 18:0 (-5.2%) and increase those of 18:2n-6, n-3 polyunsaturated FA (PUFA) and n-6 PUFA (by approx. +64%), while tended (P<0.10) to decrease trans-10 18:1 (-9%) and enhance trans-11 18:1 (+14%). These changes were accompanied by increases in the mean value of odd- and branched-chain FA, as well as in some keto-FA concentrations (P<0.05). On the other hand, it had no significant effects on the rumen fermentation characteristics that were analyzed (e.g., gas production kinetic, extent of OM degradation, pH, or ammonia and VFA concentrations; P>0.10). Although positive, when explored at practical doses in terms of animal feeding, results on the use of tannins to modulate microbial BH are not as promising as initially expected. More research in this field is still necessary.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)